Informal powers at the Court of Madrid in the last third of the 17th century: The business agents of the Indies - Andújar Castillo, Francisco (2024)
This article studies the business agents who proved an essential link between the various territories of the Hispanic monarchy and the Court of Madrid. They acted as mediators between those who resided in America and sought to obtain positions and honors that the monarch dispensed. However, from 1674 onwards, when positions of political government, as well as those of justice from 1683 onwards, began to be granted in return for money, these business agents or “brokers” also began to serve as financiers. In particular, the case of the principle agent from the last third of the 17th century, Diego de Villatoro, Marquis of Castillo and attorney of the Consulate of Lima before the Council of the Indies, is studied.